Legal Implications for Parties Who Display Inappropriate Content Through Social Media Platforms (Copyright Study) - Perdana, Satria; ., Saidin; Ginting, Budiman; Keizerina Devi, T. (KnE Social Sciences, 2024)
Copyright is one of the rights included in protected intellectual property rights. One form of creation protected by the expert is the work of photography and cinematography. However, it is known that with the development of existing technology, works in the form of photography and cinematography are often used by other parties/people by showing and/or uploading the work to social media without permission from the creator himself. It is not uncommon for the photography and cinematography created to have economic value. Another problem arises when it turns out that the photography and cinematography created contain immoral elements. Therefore, a more in-depth study is needed regarding the legal implications of uploading photography and cinematography without the author’s permission and the limits given by the norms of decency in producing the creation itself. Based on the research results, it is known that the legal responsibility of the party who shows photography and cinematography without the author’s permission on social media platforms, namely if the action is to obtain economic/commercial benefits. It is proven that if the creator suffers economic losses, then the perpetrator can be charged compensation. This type of research is normative juridical/normative legal research, which uses secondary data by processing data derived from legal materials, namely primary, secondary, and tertiary legal materials. Study data were collected through documents and qualitative analysis. Keywords: copyright, intellectual property rights, information and electronic transaction law, photography, cinematography, social media